A study of thermal properties of wool/hollow polyester needle punched nonwoven fabrics - Carvalho, Raquel Sofia Oliveira (2017)
Thermal property of the fabrics which are used in day to day activities is important one to provide comfort to human beings. The thermal properties of the textile materials depend on their thermal conductivity, thickness, density and thermal emission properties. The main objective of this research works is to analysis of the thermal properties of needle punched nonwoven fabrics manufactured from wool hybrid fibres in terms of thermal conductivity or thermal resistance. The thermal properties of the nonwoven fabrics were carried out using ALAMBETA equipment. The results show that the nonwoven fabric produced from wool/hollow polyester (50%/50%) exhibited less thermal conductivity.